Association between Exclusive Breastfeeding and Child Development - Khudri, Ghaniyyatul; Fadlyana, Eddy; Sylviana, Nova (Althea Medical Journal, 2016)
Background: Child development highly correlates with childâs quality. The fastest child development period is during the first three years, also called golden period. This research was aimed to discover correlation between exclussive breastfeeding and child development in Cipacing Village Jatinangor, district of Sumedang.Methods: This research was conducted using cross-sectional method in thirteen Pos Pelayanan Terpadu (Posyandu) Cipacing Village in Jatinangor. One hundred and two children aged 12â24 months with their caregiver were recruited as respondents by using cluster sampling method. Hist ory of exclusive breastfeeding was assessed with questionnaire while child development status was assesed with Kuesioner Pra Skrining Perkembangan (KPSP) in September 2013 after informed consent was obtained. Chi-square test analysis was performed to determine correlation between exclusive breastfeeding and child development status.Results: Overall, children in Cipacing Village had non-exclusive breastfeeding history (83.3%), and only 16.7% respondents had exclusive breastfeeding history. Meanwhile, 89.2% of children had normal development status, and 10.8% had delayed development status. Statistic analysis using chi-square test in the level of 95% confidence between exclusive breastfeeding and child development showed p=0.686 and odds ratio 2.133.Conclusions: There is no significant relationship between history of exclusive breastfeeding and child development status. [AMJ.2016;3(1):79â84]Â DOI:Â 10.15850/amj.v3n1.726